Efficacy and Safety of Dimeticone in the Treatment of Lice Infestation through Prophylaxis of Classmates - Pietro Ferrara; Francesca Del Bufalo; Valerio Romano; Eloisa Tiberi; Giorgia Bottaro; Lorenza Romani; Monica Malamisura; Francesca Ianniello; Laura Ceni; Giovanni Mottini; Antonio Gatto (Tehran University of Medical Sciences, 2013)
Background: We conducted a study to evaluate efficacy and safety of dimeticone 4%, a lotion with no conventional insecticide activity, to cure lice infection and to prevent spread of infestation/reinfestation by prophylaxis of classmates.Methods: The study is carried out between April 2008 and June 2008 in Petranova International Institute in Rome. A total of 131 children, aged 3 to 13 years (median age: 7 years) were included in the study. All participants received treatment with dimeticone 4% that was applied both to children with the infestation, to cure it, and to all classmates, to prevent the spreading of the infestation. They have been controlled after 7 and 30 days from the application of dimeticone.Results: At baseline we found a positivity of lice infestation in 23/131 children (17.6%), whereas 108/131 (82.4%) children were free from lice. After 7 days of treatment with dimeticone 4%, 7/23 (30.4%) positive children still had lice infestation, with a cure rate of 69.6% (16/23). At 30 days 26/131 children (19.9%) were infested: 15 children were lice free at baseline whereas 11 had lice at both evaluations; the cure rate amounted to 52.2% (12/23). The reinfestation rate (percentage of positive children that showed negativity at baseline) was 5.3% (7/131) at 7 days and 11.5% (15/131) at 30 days.Conclusion: The lower reinfestation rate showed in our trial suggests that this approach could be effective in reducing spreading of head lice in small communities. More studies are needed to confirm our findings